Inquiry Learning: Upaya Meningkatkan Hasil Belajar IPS pada Siswa MTs Negeri 4 Gunungkidul - Ari Endah Widyaningsih (Jurnal Pendidikan Madrasah, 2022)
This research aims to improve student learning outcomes through the application of inquiry learning models. The subject of this study is a student of class VII-C MTs N 4 Gunungkidul on IPS subjects in Interspace Interaction material. The application of the inquiry learning model in this study is carried out with several phases, namely identification and clarification of problems, making hypotheses, data collection, data analysis, and drawing conclusions. This research is best practice. There are several results of applying the inquiry learning model, namely helping learners in developing contextual learning concepts; increase the motivation and activities of learners in IPS learning; and increase information about the concept of interaction between rooms learned through activities using systematic LKPD. The inquiry learning model can be applied to students at the Madrasah Tsanawiyah level.